The Relationship between Parenting Style and Social-Emotional Development of Early Childhood at RA Al-Maunah Gebang Anom Semarang - M. A. Wulanda Wardani; Endang Surani; Muliatul Jannah (Universitas Islam Sultan Agung, 2023)
The main problem of early childhood learning is social-emotional development. This learning becomes the basis for other intelligence. The purpose of this study was to determine the relationship between parenting parents with emotional social development in early childhood. The researcher's approach is quantitative using a cross sectional approach, which is observation in one time. Data collection uses parenting questionnaire and KMME. The data obtained can be important for normality and reliability testing. Normality test is done to find out whether the data used in the study has a normal distribution and the results of the reliability test for all research variables have a Cronbach alpha value of> 0.60 so that it can be said that the instruments in this study are reliable and feasible to use. The results of this study indicate the relationship of parenting parents with social emotional development in early childhood, the chi square results show that the value of the Chi-Square Test symptom is P = 0.015